Juvenility in Rubberwood (Hevea Brasiliensis) and its Relation with the Physical and Mechanical Properties - Mohamad, Roslan (1998)
Knowledge on anatomical, physical and mechanical properties of wood is necessary in assessing the potential utilisation of wood. The main objectives of this study are to determine the cellular composition and anatomical variations of juvenile rubberwood (Hevea brasiliensis) and their extent in the selected clones and age groups. Another objective is to determine the structure of juvenile wood in relation to physical and mechanical properties. Three different clones, PB 359, PB 3 66 and RRIM 600 from two age groups, namely 10 and 22 years old were selected from Golden Hope Plantation Bhd. Three trees were felled for each clone and age group. Each tree was divided into three portions along the height namely, stump (S₁), trunk (S₃) and branch (S₅). Outer and inner samples along the radial position were chosen for comparative studies on the anatomical, physical and mechanical properties. All samples for each test were prepared in accordance with the British Standard (BS 373:1957) specifications.